Neuropathologic correlates of shape of subcortical brain structures. (December 2021) - Makkinejad, Nazanin; Tamhane, Ashish A; Bennett, David A.; Schneider, Julie A.; Gutman, Boris A; Arfanakis, Konstantinos
Abstract: Background: Age‐related neuropathologies have devastating effects on subcortical brain structures. MRI can be used to explore patterns of atrophy associated with various diseases, however, definitive diagnosis of age‐related neuropathologies is only possible at autopsy. The purpose of this work was to combine ex‐vivo MRI and detailed neuropathology in a large community cohort of older adults to conduct the most comprehensive investigation to‐date on the association of age‐related neuropathologies with the shape of subcortical brain structures. Method: Cerebral hemispheres were obtained from 814 participants of the Rush Memory and Aging Project and Religious Orders Study, two longitudinal cohort studies of aging (Fig. 1). A single brain hemisphere from each participant was imaged ex‐vivo on a clinical 3T MRI scanner, while immersed in 4% formaldehyde solution. Following ex‐vivo MRI, all hemispheres underwent detailed neuropathologic examination by a board‐certified neuropathologist blinded to clinical and imaging findings (Fig. 2). T2‐weighted images from all hemispheres were used to segment nucleus accumbens, amygdala, caudate, hippocampus, putamen, and thalamus. Subcortical shape measures were computed using the ENIGMA‐Shape protocol. Vertex‐wise linear regression was performed for each subcortical structure, modeling the logarithm of the Jacobian determinant at each vertex as a function of a comprehensive list of age‐related neuropathologies controlling for demographics and scanners. The analysis first considered data from all hemispheres (left hemispheres were mirrored to appear like right hemispheres and the opposite), and then was repeated considering left and right hemispheres separately. Result: When considering all hemispheres (Fig. 3), Alzheimer's pathology, atherosclerosis, and TDP‐43 pathology were all associated with unique patterns of inward deformation of the hippocampus and amygdala. When considering left and right hemispheres separately (Fig. 4), the results were relatively similar to the combined analysis. Also, when considering the right hemispheres alone, arteriolosclerosis was associated with inward deformation of the putamen and thalamus. Lewy bodies, infarcts and cerebral amyloid angiopathy did not show any links to the shape of subcortical brain structures. Conclusion: Among the different age‐related neuropathologies, Alzheimer's pathology, TDP‐43 pathology, atherosclerosis and arteriolosclerosis are the ones that have independent contributions on shape abnormalities of subcortical brain structures that could potentially contribute towards in‐vivo prediction of these neuropathologies.